Application of EMPC for precise position control of DC-motor system with Backlash. (July 2020) - M.A., Aravind; N.S., Dinesh; Rajanna, K.
Abstract: This paper presents design of a modified controller based on the concept of Experience Mapping based Predictive Controller (EMPC) for precise position control of DC motor system containing backlash. The earlier design of EMPC addresses well-damped and under-damped systems. However, the control action is not suitable for systems containing backlash as it produces undesirable oscillations. The proposed design modifies the control action to include a separate action in the backlash region for both the well damped and under-damped position system using an Experience Mapped Knowledge(EMK). The simulation results show that the proposed controller performs well compared to previous EMPC techniques and it is also practically demonstrated on a test setup consisting of a backlash system. The simulation results are also compared with Model Reference Adaptive Controller for changes in system parameters like static friction and load inertia. Highlights: Design of intelligent controller for systems consisting of a backlash. Iterative Learning Control with adaptation. Simulation of results for changes in friction and inertia. Practical test bed construction with results.